2012
DOI: 10.1111/j.1467-8535.2012.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing future educational technologists' intentions to participate in online teaching

Abstract: Education through the Internet is being shaped by the next wave of Web technology where productivity, collaborative tools and the ubiquity of computers play a major role in changing methods of peer interaction and collaboration. Because future educational technologists will play vital roles in navigating through this technical complexity and exploring potential learning opportunities, it is imperative to understand their intentions to participate in online teaching. This study adopted Ajzen's Theory of Planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 25 publications
8
47
3
Order By: Relevance
“…Instead, the main factors influencing teachers' behavioral intentions were their personal or endogenous factors, including their attitudes and perceived behavioral control in relation to web-based professional development. The results of our study differed from the findings of Giannakos and Vlamos (2013) and those of Hung and Jeng (2013). This discrepancy may reflect the fact that these studies primarily considered the use of software or platforms; if the requirements for using these were standardized by education authorities, such external factors would have a direct impact on teachers.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Instead, the main factors influencing teachers' behavioral intentions were their personal or endogenous factors, including their attitudes and perceived behavioral control in relation to web-based professional development. The results of our study differed from the findings of Giannakos and Vlamos (2013) and those of Hung and Jeng (2013). This discrepancy may reflect the fact that these studies primarily considered the use of software or platforms; if the requirements for using these were standardized by education authorities, such external factors would have a direct impact on teachers.…”
Section: Discussioncontrasting
confidence: 99%
“…We adopted the web-based Professional Development Attitude Scale developed by Kao and Tsai (2009) and evaluated elementary school teachers' attitudes toward web-based professional development from four perspectives: usefulness, ease of use, emotion, and behavior. Lee, Cerreto, and Lee (2010) found that the explanatory power of attitudes with regard to behavioral intention was twice that of subjective norms and three times that of perceived behavioral control, indicating that attitudes exert a critical influence on behavioral intention, a finding broadly supported by Hung and Jeng (2013). These studies showed that, as is the case with subjective norms, attitudes are closely related to behavioral intention and are therefore worthy of further investigation.…”
Section: Attitudes Toward Web-based Professional Developmentmentioning
confidence: 84%
See 3 more Smart Citations